Different Clinical Presentations of Brucellosis - Hasanjani Roushan, Mohammad Reza (Jundishapur J Microbiol, 2016)
BACKGROUND: Brucellosis is one of the important multi-organ zoonotic infectious diseases. The forms of the clinical course of brucellosis in humans are acute, sub-acute and chronic. OBJECTIVES: The present study aimed to retrospectively analyze the clinical characteristics and complications in the clinical forms of human brucellosis in Iran. PATIENTS AND METHODS: The population included 957 patients admitted in the infectious diseases clinic affiliated to Babol University of Medical Sciences, Babol, Iran, within the past two decades. Data for the patients were obtained and documented in questionnaires. Patients were divided into three groups according to their history, symptoms and clinical presentation time: acute (0 - 2 months), sub-acute (3 - 12 months), and chronic (> 1 year). RESULTS: Most of the patients (73.8%) were in the acute stages of brucellosis, 22.6% had sub-acute brucellosis and 3.7% had chronic brucellosis. The most frequently observed symptoms were arthralgia (71%), sweating (66.7%), fever (57.2%) and backache (39.3%). The most common complication was arthritis (13.2%) in this study. CONCLUSIONS: This infection was observed with a diversity of clinical manifestations. Therefore, diagnostic difficulty because of the various clinical presentations and the way to find undiagnosed complications should be investigated in the differential diagnosis of other diseases.